Culture and paralinguistic features ~!^^:-): East meets West in a virtual exchange between South Korea and England - Michelle Wylie (University of Groningen Press, 2020)
This paper investigates whether cultural differences are apparent in the paralinguistic features used by culturally diverse interactants online. Paralinguistic features are used pervasively in digital discourse (Herring & Androutsopoulos, 2015), therefore they play a pivotal role in online communication skills. Paralinguistic features such as the innovative use of punctuation and typographical features as well as emoticons and emojis are used to add nuance, emotional tone, and to manage discourse in online communication. However, the effectiveness of these paralinguistic features is dependent upon a shared understanding of their functions. This study seeks to explore any potential cultural manifestations in the use of paralinguistic features during a semester-long virtual exchange between 21 South Korean students and 25 students studying at a university in England. The dataset of 20,379 words generated during the virtual exchange was examined for cultural manifestations in paralinguistic features. As this study examines potential cultural manifestations online, it adheres to a culturally relativist perspective, therefore an inductive approach to the analysis of the data was taken. The analysis of the data revealed culturally specific paralinguistic features with the emergence of a feature that, to the best of my knowledge, has not been recorded in previous virtual exchange research.